Preslaughter Handling and Slaughter of Meat Animals 2022
DOI: 10.3920/978-90-8686-924-4_1
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 1: Quantifying animal welfare preslaughter using behavioural, physiological and carcass and meat quality measures

Abstract: Animal welfare and stress refer to the subjective experience of the animal, which depends on its emotional and cognitive capacities to evaluate the situation it is in, to know its body state in terms of needs, and the higher-order, conscious, processing of the information. The origin of stress-inducing factors may be psychological, such as fear, or physical, such as food deprivation. In both cases, they influence the emotional status of the animal. Due to its subjective, therefore unmeasurable, character, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 472 publications
0
10
0
1
Order By: Relevance
“…hypoglycaemia and reduced liver and muscle glycogen concentration) and the accumulation of metabolites, e.g. blood and muscle lactate concentration (Frese et al, 2016) in response to prolonged and anaerobic exercise, might be associated with fatigue (Terlouw and Bourguet, 2022). Yu et al (2009) reported increased blood plasma CK and LDH levels after transport of finishers for 1, 2 or 4 h, respectively.…”
Section: E) Resting Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…hypoglycaemia and reduced liver and muscle glycogen concentration) and the accumulation of metabolites, e.g. blood and muscle lactate concentration (Frese et al, 2016) in response to prolonged and anaerobic exercise, might be associated with fatigue (Terlouw and Bourguet, 2022). Yu et al (2009) reported increased blood plasma CK and LDH levels after transport of finishers for 1, 2 or 4 h, respectively.…”
Section: E) Resting Problemsmentioning
confidence: 99%
“…Definition : Glucose is a monosaccharide, which can be stored as a multi‐branched polysaccharide, called glycogen, in skeletal muscle and the liver (Terlouw and Bourguet, 2022). In monogastric animals, like pigs, blood glucose levels reflect the nutritional status of the animal (Shaw and Tume, 1992).…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Уровень стрессовой нагрузки на животное зависит от характера, интенсивности и продолжительности негативных раздражителей в сочетании с восприимчивостью самих животных [7,8]. В конечном итоге это приводит к снижению качественных характеристик мяса: нежности, цветности, pH и других [9,10,11].…”
Section: оригинальные статьи: зоотехния / оRiginal Scientific Article...unclassified
“…It is a traumatic experience with long-term implications for animal welfare and meat quality. High ambient temperature causes physiological stress reactions in animals while transporting them from the farm to the abattoir (Terlouw and Bourguet, 2022). When animals are put through stressful situations, their sympathetic nervous system sets in.…”
Section: Introductionmentioning
confidence: 99%